Regime shifts in demersal assemblages of the Benguela Current Large Marine Ecosystem: a comparative assessment. (March 2015) - Kirkman, Stephen P.; Yemane, Dawit; Atkinson, Lara J.; Kathena, John; Nsiangango, Silvi E.; Singh, Larvika; Axelsen, Bjorn E.; Samaai, Toufiek
Abstract: Using long‐term survey data, changes in demersal faunal communities in the Benguela Current Large Marine Ecosystem were analysed at community and population levels to provide a comparative overview of the occurrence and timing of regime shifts. For South Africa, the timing of a community‐level shift observed in the early 1990s, and of a lesser shift observed in the mid‐2000s, corresponded well with the results of other studies that showed environmental, community‐level or population‐level changes at similar times, suggesting that environmental forcing had played a role. Several population‐level shifts were detected for Namibia; these and a regime shift in the overall community identified for this country corresponded well to the timing of severe environmental perturbations and an extensive regime shift in the pelagic ecosystem of this area. However, the interpretation of these shifts was confounded by changes in sampling gear; closer scrutiny of the types of species affected and the direction of shifts (increase/decrease) in relation to the timing and nature of sampling gear modifications, revealed that the observed shifts were potentially an artefact of gear changes. This highlighted the importance of accounting for changes in sampling protocols during the analysis and interpretation of long‐term data. For Angola, a community level shift in the mid‐2000s and population‐level changes for a few species (mainly positive), could not have been influenced by gear changes which took place mainly before the onset of the time series under consideration. However, no clear environmental or anthropogenic changes that could have influenced these shifts were obvious.